Pemikiran Islam Tentang Konsep Perubahan Sosial Islam - Ab. Majid, Mohamad Kamil (Jurnal Usuluddin, 1998)
The article tries to elaborate the meaning of social change in the Islamic perspective. The views of Muslim scholars from Ibn Khaldun to Malik Ibn Nabi are put forward to be compared with dominant but controversial world-view concerning social change of the West of the 18th and 19th centuries.